SPEECH ACTIVITY AND ITS TYPES. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
When students get poor marks on writing assignments, it is often because they don’t have a solid grasp of the parts of speech and how they function. Parts of speech is a topic that needs to be revisited regularly in order for it to stick, but maybe you’re a busy teacher who doesn’t have time to rework every activity you know! This article provides information on the correct analysis and study of speech activity in foreign languages.